Monoclonal gammopathy in WHIM syndrome can mask hypogammaglobulinemia - Julia Lew, MD; Adil Adatia, MD (Journal of Allergy and Clinical Immunology: Global)
Monoclonal gammopathy can be seen at an early age in patients with warts-hypogammaglobulinemia, infections, and myelokathexis syndrome and can mask the presence of hypogammaglobulinemia.